Anti-MDA5 autoantibodies associated with juvenile dermatomyositis constitute a distinct phenotype in North America. (3rd November 2020) - Mamyrova, Gulnara; Kishi, Takayuki; Shi, Min; Targoff, Ira N; Huber, Adam M; Curiel, Rodolfo V; Miller, Frederick W; Rider, Lisa G; ,
Abstract: Objective: Myositis-specific autoantibodies have defined distinct phenotypes of patients with juvenile myositis (JIIM). We assessed the frequency and clinical significance of anti-melanoma differentiation-associated gene 5 (MDA5) autoantibody-associated JIIM in a North American registry. Methods: Retrospective examination of the characteristics of 35 JIIM patients with anti-MDA5 autoantibodies was performed, and differences from other myositis-specific autoantibody groups were evaluated. Results: Anti-MDA5 autoantibodies were present in 35/453 (7.7%) of JIIM patients and associated with older age at diagnosis, and lower serum creatine kinase and aldolase levels. Patients with anti-MDA5 autoantibodies had more frequent weight loss, adenopathy, arthritis, interstitial lung disease (ILD), and less frequent falling compared with anti-transcriptional intermediary factor 1 (TIF1), anti-nuclear matrix protein 2 (NXP2) and myositis-specific autoantibody/myositis-associated autoantibody-negative patients. They had a different season of diagnosis and less frequent mechanic's hands and ILD compared with those with anti-synthetase autoantibodies. Anti-MDA5 patients received fewer medications compared with anti-TIF1, and corticosteroid treatment was shorter compared with anti-TIF1 and anti-nuclear matrix protein 2 autoantibody groups. The frequency of remission was higher in anti-MDA5 than anti-synthetase autoantibody-positive JIIM. In multivariable analyses, weight loss, arthritis and arthralgia were most strongly associated with anti-MDA5 autoantibody-positive JIIM. Conclusion: Anti-MDA5 JIIM is a distinct subset, with frequent arthritis, weight loss, adenopathy and less severe myositis, and is also associated with ILD. Anti-MDA5 is distinguished from anti-synthetase autoantibody-positive JIIM by less frequent ILD, lower creatine kinase levels and differing seasons of diagnosis. Anti-MDA5 has comparable outcomes, but with the ability to discontinue steroids more rapidly and less frequent flares compared with anti-TIF1 autoantibodies, and more frequent remission compared with anti-synthetase JIIM patients.